2023
DOI: 10.1002/agr.21855
|View full text |Cite
|
Sign up to set email alerts
|

Can homestead gardens improve rural households' vegetable consumption? Evidence from three provinces in China

Taian Deng,
Marrit van den Berg,
Nico Heerink
et al.

Abstract: Vegetables play a vital role in human health. However, the average vegetable consumption among Chinese rural residents does not meet the minimum intake (300 g/adult person/day) recommended by the Chinese Dietary Guidelines. Homestead gardening—defined as growing vegetables or other food for home consumption, usually in the backyard of the household or on collectively allocated garden land—can play a significant role in promoting vegetable consumption in rural areas of developing countries. But empirical eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…In China, there are significant differences in nutrition levels between urban and rural areas [ 1 ], and rural residents are at risk of malnutrition and micronutrient deficiency [ 2 , 3 , 4 ]. Farmers’ consumption of food is insufficient, including both plant food [ 5 ] and animal food [ 6 ]. Many rural low-income families’ daily diet is only based on grains, lacking the consumption of vegetables, fruits, meat, dairy products, and other foods [ 7 ], resulting in micronutrient deficiency and dietary imbalance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, there are significant differences in nutrition levels between urban and rural areas [ 1 ], and rural residents are at risk of malnutrition and micronutrient deficiency [ 2 , 3 , 4 ]. Farmers’ consumption of food is insufficient, including both plant food [ 5 ] and animal food [ 6 ]. Many rural low-income families’ daily diet is only based on grains, lacking the consumption of vegetables, fruits, meat, dairy products, and other foods [ 7 ], resulting in micronutrient deficiency and dietary imbalance.…”
Section: Introductionmentioning
confidence: 99%
“…Plant-based foods are rich in vitamins and minerals that help prevent cardiovascular disease, maintain a healthy weight, and extend life [ 5 , 8 , 9 ]. It has been shown that an inadequate intake of fruits and vegetables contributes to nearly 3 million deaths from heart disease and stroke each year globally [ 10 ].…”
Section: Introductionmentioning
confidence: 99%